Bible Literacy for the Formation of Papuan Rural Servants of God at the Indonesia Cross-Cultural Institute - Waromij, Neles Bernhard; Jura, Demsy (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
The indigenous population of Papua consists of various tribes, cultures, and languages, and they inhabit the coast, riverbanks, valleys and mountains, with the majority adhering to Christianity. As Christians, most Papuans believe in the Bible as their source of teaching and guidance. Unfortunately, until now, the Papuan people have experienced various limitations in teaching the Holy Bible. Tribal languages are one of the causes of the obstacles in question, so it is related to teaching and faith formation in several places that use local languages. This encourages local people called to the ministry to equip themselves with Bible knowledge and skills that will hopefully enable them to develop themselves to serve the people in the area in question. Researchers conducted a study of students at the Indonesia Cross-Cultural Institute. They found that literacy became the main obstacle for local missionaries in the interior of Papua in interpreting the contents of the Bible. The process of fostering students at Indonesia Cross-Cultural Institute includes three essential things: the Stage of Knowledge of God, the Stage of Character Building, and the Stage of Knowledge and Skills. The method used in writing this article is qualitative research conducted through interviews and literature studies. Finally, this article proposes steps churches and education providers can take for prospective church service workers in Papua.